2007
DOI: 10.1111/j.1365-2842.2006.01675.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal expansion mismatch and fatigue loading on phase changes in porcelain veneered Y‐TZP zirconia discs

Abstract: There is a rapidly growing interest for the use of Y-TZP zirconia as core material in veneered all-ceramic prostheses. It was hypothesized that a mismatch in coefficient of thermal expansion between the veneering porcelain and the Y-TZP zirconia core of these prostheses causes transformation of the tetragonal to the monoclinic structure in Y-TZP zirconia at the interface boundary when exposed to fatigue loading, resulting in fracture at the interface boundary. Y-TZP zirconia discs were veneered with three porc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 18 publications
5
31
0
6
Order By: Relevance
“…Mixed and cohesive fracture patterns are clinically preferable to total adhesive types of failure, since adhesive failure is usually attributed to low bond strength values. 28 Although there are studies indicating that air abrasion using Al 2 O 3 particles affect the surface of zirconia ceramics, leading to a reduction in the flexural strength of these ceramics, 41 there are other studies that have shown that air abrasion using Al 2 O 3 particles 25,33,41,[43][44][45] and silica coating using the Rocatec system (110 µm) 46 might even strengthen zirconia ceramics, suggesting that air abrasion induced a tetragonal to monoclinic phase transformation on the Y-TZP surface. However, Qeblawi and others 43 reported that no changes in the flexural strength of Y-TZP occurred when silica-coated alumina particles (30 µm) were applied on the Y-TZP surface.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed and cohesive fracture patterns are clinically preferable to total adhesive types of failure, since adhesive failure is usually attributed to low bond strength values. 28 Although there are studies indicating that air abrasion using Al 2 O 3 particles affect the surface of zirconia ceramics, leading to a reduction in the flexural strength of these ceramics, 41 there are other studies that have shown that air abrasion using Al 2 O 3 particles 25,33,41,[43][44][45] and silica coating using the Rocatec system (110 µm) 46 might even strengthen zirconia ceramics, suggesting that air abrasion induced a tetragonal to monoclinic phase transformation on the Y-TZP surface. However, Qeblawi and others 43 reported that no changes in the flexural strength of Y-TZP occurred when silica-coated alumina particles (30 µm) were applied on the Y-TZP surface.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al [54] suggested that the ceramic firing temperature should not affect the zirconia core material. This statement is supported by some studies where X-ray diffraction analysis was made and no zirconia transformation from tetragonal to monoclinic phase was observed during the ceramic firing procedure [55]. Oilo et al [56] reported that flexural strength of zirconia core material is reduced after first firing, though it not further affected by following firings.…”
Section: Discussionmentioning
confidence: 80%
“…The possible effect of multiple firings has also been investigated. It has been reported that the number of firings does not influence the strength of zirconia itself [54][55][56], while it has been reported to affect the bond strength to the core material [57][58][59] as well as the flexural resistance of the veneering ceramic tested without the zirconia substrate [60]. No literature indications were found about flexural resistance of veneering layer in a bi-layered specimen, with the veneering ceramic fired on a zirconia substrate.…”
Section: Introductionmentioning
confidence: 99%
“…1 Algunos autores han observado un patrón de fractura de los especímenes de recubrimiento cerámico de tipo adhesivo a nivel de la interfaz, este modo de falla es comparable con los resultados de otros estudios de laboratorio. [2][3][4][5] Guess y col. y otros investigadores han concluido que la deslaminacion del recubrimiento cerámico ocurre por la deficiente adhesión interfacial y la gran resistencia a la fractura que puede detener, orientar y propagar los cracks hacia la interfaz; 6-8 en este estudio se observó lo ya sugerido. Sin embargo, para entender las altas tasas de deslaminación y fractura de las cerámicas de recubrimiento en estudios clínicos, se requeriría de más investigaciones para evaluar los mecanismos de unión de los sistemas cerámica-dióxido de zirconio.…”
Section: Discussionunclassified